2011
DOI: 10.1016/j.ygyno.2010.12.340
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of vulvar intraepithelial neoplasia with topical imiquimod: Seven years median follow-up of a randomized clinical trial

Abstract: In case of a complete response, imiquimod is effective in the long-term. Furthermore, patients with a long-term complete response had a significantly better global quality of life than patients who recurred after imiquimod treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 27 publications
1
78
0
1
Order By: Relevance
“…24 Recurrences after imiquimod are established at approximately 20.5% versus 53.5% after surgical therapies. 35,36 The small number of patients treated with imiquimod in our group, however, show comparable results to excision regarding RFS in univariate analyses (Fig. 1).…”
Section: Discussionmentioning
confidence: 49%
“…24 Recurrences after imiquimod are established at approximately 20.5% versus 53.5% after surgical therapies. 35,36 The small number of patients treated with imiquimod in our group, however, show comparable results to excision regarding RFS in univariate analyses (Fig. 1).…”
Section: Discussionmentioning
confidence: 49%
“…In the largest prospective, randomized, double-blinded, and placebo-controlled study [62] with 52 patients, a 35% complete response and 46% partial response was found. After a median follow-up of 7.2 years, VIN recurred in only one of the complete respondents, suggesting that imiquimod is effective in the long term [63].…”
Section: Imiquimodmentioning
confidence: 97%
“…En 2011, Terlou et al ont publié les ré sultats de suivi à 7 ans des patientes traité es par imiquimod dans la cohorte de van Seters [16]. Parmi les 26 patientes initialement traité es par imiquimod, 24 ont pu être ré é valué es à 7 ans et 2 patientes non revues ont pu donner les informations né cessaires sur l'é volution de leur maladie.…”
Section: Diffé Rentes Modalité S Thé Rapeutiquesunclassified